STUDY EKONOMI SYARIAH TENTANG KONSEP SYUKUR BARAT DALAM KESEDERHANAAN DAN PERILAKU ZIS (Equilibrium: Jurnal Ekonomi Syariah, 2019)
The concept of gratitude raised in this paper is the concept of Western gratitude, the meaning of gratitude which is a feeling of happiness as a reaction to get something that is expected to be real from a certain person or when the peace that is obtained from natural beauty. The concept of Western gratitude that eliminates the divine aspect. So in this paper, we try to analyze the concept of Western gratitude for the effect on the individual person as seen from the simplicity of life and the effect on the environment seen in ZIS behavior. The findings of this research that contextual gratitude can have a positive impact on oneself that is living a life of simplicity, but if seen explicitly will not get anything even wasteful life because the purpose of his life is to find satisfaction alone and even self-oriented principles even want-oriented do not care for others if in Islam in the form of ZIS. The implication of this research is that gratitude to God is realized by carrying out God's commands and prohibitions in carrying out Islamic law and gratitude to humans is realized by becoming simpler in running life and increasingly becoming an example for the community environment and more generous for the people underneath and prefer to care for others human. They are more diligent in running as people who fear Allah, both the obligatory and the sunnah.